The challenges of tuberculosis control in protracted conflict: The case of Syria. (January 2020) - Abbara, Aula; Almalla, Mohamed; AlMasri, Ibrahim; AlKabbani, Hussam; Karah, Nabil; El-Amin, Wael; Rajan, Latha; Rahhal, Ibrahim; Alabbas, Mohammad; Sahloul, Zaher; Tarakji, Ahmad; Sparrow, Annie
Highlights: The conflict has decimated Syria's health system, destroying key infrastructure. The extent of tuberculosis (TB) in Syria, particularly the extent of drug resistance is unknown. Addressing TB among vulnerable populations is key to TB control in Syria. Failure to address TB within Syria's borders impacts refugee destination countries. Innovative measures for case finding, diagnosis, and management in conflict are needed. Abstract: Objectives: Syria's protracted conflict has resulted in ideal conditions for the transmission of tuberculosis (TB) and the cultivation of drug-resistant strains. This paper compares TB control in Syria before and after the conflict using available data, examines the barriers posed by protracted conflict and those specific to Syria, and discusses what measures can be taken to address the control of TB in Syria. Results: Forced mass displacement and systematic violations of humanitarian law have resulted in overcrowding and the destruction of key infrastructure, leading to an increased risk of both drug-sensitive and resistant TB, while restricting the ability to diagnose, trace contacts, treat, and follow-up. Pre-conflict, TB in Syria was officially reported at 22 per 100 000 population; the official figure for 2017 of 19 per 100 000 is likely a vast underestimate given the challenges and barriers to case detection. Limited diagnostics also affect the diagnosis of multidrug- and rifampicin-resistant TB, reported as comprising 8.8% of new diagnoses in 2017. Conclusions: The control of TB in Syria requires a multipronged, tailored, and pragmatic approach to improve timely diagnosis, increase detection, stop transmission, and mitigate the risk of drug resistance. Solutions must also consider vulnerable populations such as imprisoned and besieged communities where the risk of drug resistance is particularly high, and must recognize the limitations of national programming. Strengthening capacity to control TB in Syria with particular attention to these factors will positively impact other parallel conditions; this is key as attention turns to post-conflict reconstruction.